Educating Exceptional Children - Kirk, Samuel A. and Gallagher, James J. (Boston Houghton Mifflin Company, 1986)
EDUCATING EXCEPTIONAL CHILDREN, INTERNATIONAL EDITION is a comprehensive survey program that introduces students to each disability category as well as covering the needs of children who are gifted and talented. The Twelfth Edition continues to focus on the strengths previous editions, providing practical applications on adapting teaching methods, curriculum, and settings, and also offering analysis of ecological factors that influence the exceptional child in and out of the classroom. This edition features cutting-edge coverage of the new Response to Intervention Model, comprehensive and up-to-date descriptions of the strengths and weaknesses associated with each disability, the most current teaching techniques for each category, and helpful references to available.
Include Index, Glossary, References and Colored Illustrations.
Keywords: Special Education -- Special education -- United States